Yuliana Boycheva, «Αl. Kuyumdzhiev, Emm. Mutafov (επιμ.), Corpus of Mural Paintings from the first half of 19th century in Bulgaria (στα βουλγαρικά) (Corpora of Pre-Modern Christian Orthodox Mural Painting, Bulgaria 3)». - BOYCHEVA, Yuliana (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2019)
Αl. Kuyumdzhiev, Emm. Mutafov (επιμ.), Corpus of Mural Paintings from the first half of 19th century in Bulgaria (Corpora of Pre-Modern Christian Orthodox Mural Painting, Bulgaria 3), Institute of Art Studies, Bulgarian Academy of Sciences, Σόφια 2018, 900 σελ., 1.200 εικ., 46 αρχιτ. και 50 σχέδ. τοιχογραφιών (στα βουλγαρικά, ο πρόλογος και το εικονογραφικό ευρετήριο στα βουλγαρικά και τα αγγλικά). ISBN: 978-954-8594-73-8.